Maintaining spiritual and balance technology in the AI era - Trisia, Riri (Jurnal Konseling dan Pendidikan, 2025)
Artificial intelligence (AI) technology has brought about profound changes in many facets of human existence, posing new difficulties that have an impact on mental and spiritual equilibrium. With an emphasis on how people might stay connected to spiritual parts of life in the face of rapid change, this study examines the significance of preserving balance between spiritual ideals and technological advancements. To lessen the effects of "techno-stress" and alienation that people frequently experience in the digital age, an integrative strategy that incorporates mindfulness, religion-based ethics, traditional practices like meditation and dhikr, as well as universal moral standards, is suggested. While stressing the risks of utilizing AI technology without a solid ethical basis, this article also explores how it may aid in human spiritual development, for instance, through applications that promote meditation and introspection. Society may use AI as a tool to enhance life quality rather than merely increase efficiency if it embraces spirituality as a key component of interactions with the technology. This study provides guidance for creating a more meaningful and balanced existence in the high-tech age.